The Use of Serrated Razor Blade in Slicer - Remon Purba; Ainun Rohana; Saipul Bahri Daulay (Jurnal Rekayasa Pangan dan Pertanian, 2013)
One of fabricated process is slicing. This study was aimed to examine the effect of using a serrated blade on the effective capacity of the tool and the percentage of broken material on the mechanical slicer, conducted in December2012 to January 2013 in the Laboratory of Agricultural Engineering, Faculty of Agriculture, University of North Sumatra, Medan, using non-factorial completely randomized design(CRD). The parameter smeasured were the effective capacity of the tool and the percentage of broken materials. The results showed an effective tool capacity of 47.52kg/hr, 50.5 4kg/hr and73.07kg/hr respectively the percentage of unsliced material of 5.07%, 4.63% and 3.92% respectively. Keywords: blade, processing, slice, capacity.